Evaluation of antibacterial and osteogenic properties of a novel Poly (acrylic acid)-calcium-zinc biomineralized hydrogel - Xie, Xiaobin; Feng, Xiaoxiao; Hong, Lihui; Yu, Xinke; Li, Hongye; Zhang, Hao; Liu, Mingming; Wang, Yimeng (Frontiers in Materials, 2024)
Infectious bone defects are one of the thorny problems faced by orthopedists. Developing prosthetic materials with antimicrobial osteogenic features is a key solution. Biodegradable Polyacrylic acid (PAA)-based hydrogels have gained attention for their exceptional qualities. However, the influence of zinc ions on PAA-based mineralized hydrogels remains understudied. In this paper, Poly(acrylic acid)-calcium-zinc (PA-CZ) biomineralized hydrogel was prepared through ionic cross-linking and biomineralization. In vitro bacterial and cell tests demonstrated the hydrogel's exceptional biocompatibility, antibacterial, and osteogenic traits, along with good mechanical strength. The PA-CZ mineralized hydrogel lays the foundation for developing orthopedic implants with antimicrobial osteogenic features and offers a promising approach for treating infected bone defects.